Novel ACAD8 variants identified in Isobutyryl-CoA dehydrogenase deficiency: challenges in phenotypic variability and management - Tao, Yilun; Han, Dong; Li, Jianfang; Li, Xiaoyun; Hao, Luna; Song, Wenxia; Wang, Lihong; Li, Xiaoze (Frontiers in Genetics, 2025)
Isobutyryl-CoA dehydrogenase deficiency (IBDD) is a rare autosomal recessive disorder caused by biallelic variants in the ACAD8 gene, which disrupts valine metabolism. In this study, we report seven individuals identified through newborn screening (NBS) with elevated C4-acylcarnitine levels, including five confirmed patients and two heterozygous carriers. Genetic analysis identified 12 distinct ACAD8 variants, seven of which were novel (c.221C>T, c.518T>C, c.727A>G, c.868G>A, c.947A>T, c.966G>A, c.1058T>C). According to ACMG classification criteria, c.221C>T was classified as likely pathogenic, while the remaining variants were categorized as variants of uncertain significance (VUS). During a mean follow-up of 4.81 years, all patients maintained normal growth patterns but two patients developed neurological symptoms that included recurrent febrile seizures and sensory integration dysfunction. These findings expand the ACAD8 variant spectrum, highlight the phenotypic variability of IBDD, and underscore the importance of long-term follow-up and individualized management strategies.